Nutrients Ions Indices of Some Medicinal Flora of Cholistan Desert of Pakistan - Yasin, Ghulam; Altaf, Adeela; Haq, Ikram ul; Nazeer, Samra; Sabir, Mubasharah (UI Scholars Hub, 2023)
By knowing the nutritional status of a plant, one can better manage and use it for ethnobotanical purposes. Various nutrients are accumulated as osmotica in plants of stressful environments. The type and quantity of nutrients present in plants also determine the effectivity of medicine obtained from that plant. Hence, practical utilization of these plants as food or medicines needs to explore the exact nature and presence of the nutrient ions for discrimination of their toxic or medicinal nature. In the present study, some important nutrients in a number of xerophytic plants from Cholistan desert of Pakistan were quantified. Leave, stem and root specimens of seasonally available herbs, shrubs and trees were collected and analyzed for sodium, potassium and phosphorus contents. Each sample was replicated thrice. Obtained data were statistically analyzed and presented as Means ± standard deviations. Among the shrubs, maximum concentration of sodium was observed in leaves of Salsola imbricata (269.99 mg/g). The highest concentration of potassium was recorded in stem of Calotropis procera (67.78 mg/g) while maximum phosphorus was found in stem of Pseuda fruticosa (7.051 mg/g). Among the herbs, maximum sodium was found in stem of Orobanche aegyptiaca (234.95 mg/g), maximum potassium in leaves of O. aegyptiaca (270.71 mg.g) and the maximum phosphorus in root of Citrullus colocynthis (9.34 mg/g). For trees, maximum concentration of sodium, potassium and phosphorus were recorded in leaves of Tamarix aphylla (305.40 mg/g), stem of Capparis decidua (132.6 mg/g) and stem of Acacia nilotica (5.90 mg/g) respectively.